Influence of Aerobic Training in Unfit Women During Pregnancy on Infant Heart Function - Stewart, Courtney (East Carolina University, 2017)
Research has shown that women are more likely to make positive lifestyle changes, such as exercise, during pregnancy. Women, with healthy, low-risk pregnancies, free from complications, can participate in exercise throughout pregnancy based on guidelines from the American College of Obstetrics and Gynecology (ACOG), American College of Sports Medicine (ACSM), and the American Heart Association (AHA). Maternal exercise has been shown to benefit pregnant women and their children. Previous research on women that are active prior to pregnancy demonstrates exercise during pregnancy is associated with improved heart health measures, evidenced by lower HR and increased ejection fraction, in infants. However, we do not know if these benefits occur for children from women that were inactive before pregnancy. This study will address this gap by determining if heart function of infants is improved in unfit women that begin exercising during pregnancy. We hypothesize that one-month old infants of unfit women who exercise during pregnancy will have higher stroke volume, fractional shortening, and ejection fraction, lower heart rate and similar cardiac output compared to one-month old infants of unfit women that did not exercise while pregnant (controls). To test this hypothesis, inactive pregnant participants were randomized into either exercise or control group. Women in the exercise group participated in moderate intensity exercise for 50 minutes, 3 times per week from 16 weeks pregnancy until delivery; non-exercisers received no exercise intervention. After delivery, a standard (blinded) echocardiographic recording was performed on all one-month infants. Infants were classified as active or quiet activity state by a pediatric cardiologist blinded to group randomization. Data was analyzed using multiple t-test, with an alpha level set a priori at p < 0.05. Statview software was used to complete the analyses. Current findings show lower heart rate (HR) of infants from unfit women that exercised during pregnancy compared to one-month infants of unfit controls (p=0.06). Infants of unfit exercisers also have trends of increased stroke volume, ejection fraction, cardiac output, and fractional shortening in the quiet state. Cardiac output is similar in the exercise and control groups. Our current findings suggest that exercise during pregnancy, regardless of activity prior to pregnancy, may provide similar heart benefits as children of women previously healthy and trained prior to pregnancy. Ultimately, this study is the first step to begin to demonstrate that exercise during pregnancy, regardless of the mother’s prior activity levels, is the earliest intervention to decrease heart disease risk. This research is pivotal in encouraging all women, regardless of previous activity level, to begin exercise during pregnancy in order to improve the heart health for their child.
Keywords: exercise; pregnancy; infant heart function